The Influence of Student Engagement Towards Learning Achievement of School of Communication and Business Telkom University - Intan Tamara Febrinzky; Hani Gita Ayunigtias (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2020)
This study aims to determine the effect of student engagement on student achievement in the Faculty of Communication and Business, Telkom University. The aspects studied were cognitive engagement, emotional engagement and behavioral engagement in terms of student engagement. And the value of GPA for learning achievement. The method in this study uses descriptive analysis techniques with simple linear regression analysis. To collect the sample using incidental sampling technique through a questionnaire. This questionnaire was distributed to 361 students of the Faculty of Communication and Business Telkom University. From the results of tests conducted, it is found that there is a relationship between student engagement on learning achievement. Where this relationship is perfectly positive correlation. And there is no significant effect between student engagement on learning achievement.